1992
DOI: 10.1139/y92-138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-flow infusion and magnesium on tissue necrosis during regional ischemia in the canine myocardium

Abstract: Passive intracoronary perfusion of therapeutic agents has been used in the clinical setting to attenuate the effects of brief episodes of myocardial ischemia. The objective of this study was to assess the effects of low-flow coronary infusion with or without Mg2+ on tissue necrosis and cardiac hemodynamics after prolonged regional ischemia. In 33 anesthetized dogs (5 excluded during study), the left anterior descending coronary artery was occluded for 6 h. Dogs were assigned to three groups: the first group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…The ISO-induced MI disease model mimics cardiovascular stress disorders that not only produce infarction, but in which intracellular Mg 2+ deficiency may play a role. 31 , 32 Nevertheless, in our study, Mg 2+ pre-treatment did not alter infarct size, suggesting a lack of Mg 2+ cardioprotection, as also reported in other studies, 13 , 14 and at the same time, contradicting the results of some previous studies. 7 - 11 …”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The ISO-induced MI disease model mimics cardiovascular stress disorders that not only produce infarction, but in which intracellular Mg 2+ deficiency may play a role. 31 , 32 Nevertheless, in our study, Mg 2+ pre-treatment did not alter infarct size, suggesting a lack of Mg 2+ cardioprotection, as also reported in other studies, 13 , 14 and at the same time, contradicting the results of some previous studies. 7 - 11 …”
Section: Discussioncontrasting
confidence: 91%
“…In animal studies, Mg 2+ reduced infarct size 7 - 11 and inhibited myocardial apoptosis 12 under certain conditions, but not others. 13 , 14 There is therefore a need for further experimental and clinical studies on Mg 2+ therapy.…”
Section: Aimmentioning
confidence: 99%
“…Collateral blood flow (ie, subendocardial layer blood flow) during 120-minute occlusion period was not affected by treatment with MK383. Collateral blood flow is a baseline predictor of infarct size 31,32 ; an inverse relationship exists between collateral blood flow and infarct size (ie, larger infarcts with low flow and vice versa). 33,34 This relationship was found in dogs subjected to the reocclusion protocol; the relation shifted downward ( P = 0.014; mean likelihood ratio) in MK383 dogs suggesting a cardioprotective effect but protection was not caused by improved perfusion within the ischemic myocardium.…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium had no benefit on infarct size or remodeling. Kingma et al (37), using a dog permanent occlusion model, demonstrated a similar result in that no difference was demonstrated in the infarct size in dogs in whom the coronary bed distal to the occlusion was perfused with a Ringer's lactate solution with added magnesium, compared to perfusion with Ringer's lactate alone. The results of these studies suggest that the benefits of magnesium on pump function are probably related to myocardial protection involving the ischemic region rather than a global improvement in cardiac function.…”
Section: Cardioprotection: Magnesium and Total Mortality In The Postmmentioning
confidence: 84%